2011
DOI: 10.1111/j.1558-5646.2011.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Multilocus Introgression Patterns: A Case Study on the Mouse X Chromosome in Central Europe

Abstract: patibilities between interacting loci, the Bateson-DobzhanskyMuller model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 98 publications
(172 reference statements)
8
110
0
Order By: Relevance
“…To fit cline shape and position consistently for an unknown selection regime, a "concordance" method was developed by Szymura and Barton (1986) and used to analyze the hybrid zones in Bombina and, most recently, used for the hybrid zone in Mus by Macholán et al (2011). This method is similar to the one in Gompert and Buerkle (2009), which uses diploid genotype frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…To fit cline shape and position consistently for an unknown selection regime, a "concordance" method was developed by Szymura and Barton (1986) and used to analyze the hybrid zones in Bombina and, most recently, used for the hybrid zone in Mus by Macholán et al (2011). This method is similar to the one in Gompert and Buerkle (2009), which uses diploid genotype frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tests of geographical concordance and coincidence among genetic or phenotypic clines can detect variable introgression and have been used to identify loci potentially associated with reproductive isolation [19][20][21]. Genomic clines are mathematical functions that describe the probability of locus-specific ancestry along a gradient in genomewide admixture or hybrid index, which is defined as the proportion of an admixed individual's genome inherited from one of two parental populations [12,22,23], with related models in earlier studies [15,[24][25][26]. This is not a spatial gradient, rather nearly pure individuals of each parental type occupy opposite ends of the gradient.…”
Section: Introductionmentioning
confidence: 99%
“…QTLs for reduced testis weight were detected in the pseudoautosomal region and on chromosomes 2 and 4 (White et al, 2012). The pseudoautosomal region has been previously linked to meiotic arrest and F1 sterility in crosses between M. spretus and C57BL/6J (Guénet et al, 1990;Matsuda et al, 1991Matsuda et al, , 1992Hale et al, 1993 (Tucker et al, 1992;Payseur et al, 2004;Teeter et al, 2008;Macholan et al, 2011;Janoušek et al, 2012). This implies that the X chromosome is prominently involved in the establishment of reproductive isolation between the mouse subspecies in nature.…”
Section: The Large X Effect On Hybrid Sterilitymentioning
confidence: 78%
“…Haldane's rule infers the involvement of the sex chromosomes in hybrid sterility. Indeed, many quantitative trait loci (QTLs) for hybrid male sterility in mice were mapped on the X chromosome (Oka et al, 2004;Storchová et al, 2004;Good et al, 2008;White et al, 2011;Oka and Shiroishi, 2012), and limited gene flow on the X chromosome was observed between adjacent species or subspecies in natural hybrid zones (Tucker et al, 1992;Payseur et al, 2004;Teeter et al, 2008;Macholan et al, 2011;Janoušek et al, 2012). Such a disproportionate effect of X-linked loci on interspecific or intersubspecific hybrid fitness is called as "the large X effect" (Coyne and Orr, 1989).…”
Section: Introductionmentioning
confidence: 99%